Atividade fotoquímica em folhas do mamoeiro Carica papaya L. durante o período reprodutivo e caracterização da ontogenia dos frutos - Santos, Ketney Tonetto dos (2007)
In this work the photochemistry activity in leaves of plants of the papaya tree Carica papaya L. cv. Golden was evaluated fotnightly in a commercial plantation. The measures had beginning in the anthesis and concluded after the first crop (January for junho/2007). The kinetics of the emission of the fast fluorescence of the chlorophyll was she obtained with aid of a portable fluorometer (Handy-PEA, Hansatech, UK) using leaves previously adapted to the darkness. The results showed that the alterations happened in the apparel photosynthetic were more severe in the month where there was an abrupt fall in the precipitation. Low values of the initial fluorescence (F0), maximum fluorescence (FM) and of the revenue quantum potential maximum of the PS II (FV/FM) they indicated the occurrence of chronic photoinhibition in this period. For they be still scarce the studies on the chemical and biochemical changes that happen starting from the ontogeny of the fruits of the papaya tree, in this work it was also evaluated some physical changes, chemistries and biochemistries in the fruits of this the anthesis to the matureness. The activity of pectinametylesterase (PME), enzyme that prepares the substratum so that the other enzymes pectinolíticas acts in the process of matureness of these fruits, it increased starting from 120 DPA in the same way that the index of SS. On this same occasion it happened a decrease of the pH of the cellular juice and of the titratable acidity (ATTN) contained in the pulp of the fruits. These results confirm the participation of the PME, the presence of the acids organic and the beginning of the degradation of the it seems cellular before even of the crop.